Determinant of profitability Islamic banks - Handriani, Eka (JPS (Jurnal Perbankan Syariah), 2025)
Purpose – This study empirically investigates the key determinants of profitability among Islamic banks (ISBs) in Indonesia. The analysis incorporates several critical variables: bank size, liquidity, tangible assets, non-debt tax shields, growth, and bank age. Method – The sample comprises 65 financial statements and annual reports from 13 Islamic banks operating in Indonesia from 2019–2022. Data were analyzed using LISREL, employing structural equation modelling to examine the relationships among variables. The empirical findings indicate that bank size exerts a positive and statistically significant effect on profitability. Likewise, both asset structure and bank age are positively associated with improved financial performance. Conversely, bank growth and the financing-to-deposit ratio (FDR) exhibit negative but statistically insignificant effects, suggesting these variables have only a marginal influence on profitability within the context of this model. Findings – The results imply that fluctuations in FDR, whether upward or downward, do not directly contribute to meaningful changes in earnings. Instead, other internal factors appear to play a more substantial role in shaping the profitability of ISBs. Implications – Consistent with signaling theory, enhancing profitability may serve as strategic signals to investors, indicating sound management quality and promising prospects. This perceived strength encourages greater investor confidence, increasing third-party funds and capital inflows, thereby expanding financing capacity and revenue generation within Islamic banks.